2021
DOI: 10.3390/app11146318
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study of Different Types of Greek Honey as Potential Natural Antimicrobials against Dental Caries and Other Oral Pathogenic Microorganisms. Case Study Simulation of Oral Cavity Conditions

Abstract: To study the antibacterial effect of different Greek honeys, samples of citrus honey, Saturja spp. Honey, and oregano and sage honey were collected directly from producers. Manuka honey and artificial honey were used as controls. The honeys were diluted in various concentrations to determine the minimum inhibitory concentration (MIC) and were also placed in agar wells to determine the inhibitory zones of growth. The bacteria tested were two reference strains and five pathogens isolated from patients with vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 94 publications
3
15
0
Order By: Relevance
“…The results indicated that the Saturja spp. and the oregano and sage honeys exhibited a greater antibacterial activity against the tested bacteria than Manuka honey [60].…”
Section: Honeymentioning
confidence: 86%
See 1 more Smart Citation
“…The results indicated that the Saturja spp. and the oregano and sage honeys exhibited a greater antibacterial activity against the tested bacteria than Manuka honey [60].…”
Section: Honeymentioning
confidence: 86%
“…Strong activity of honey is also observed against A. viscous, A. actinomycetemcomi The graph shows mean MIC values ± SEM for honey and royal jelly expressed in % for the bacterial strains causing oral cavity infections. Only experiments in which the MIC value was determined in % were included in the analysis [5,41,43,44,46,48,49,52,54,56,[58][59][60]. (B) The graph shows mean MIC values ± SEM for honey, royal jelly, and bee venom expressed in µg/mL for the bacterial strains causing oral cavity infections.…”
Section: Bee Venommentioning
confidence: 99%
“…Although the studies performed have suggested the limited efficacy of honey against S. mutans , a very recent laboratory observation with different Greek honey types and manuka honey revealed that all tested honey samples were highly effective against S. mutans [ 53 ]. The average MIC values of citrus (n = 20), Satureja spp.…”
Section: Honey—its Composition and Antibacterial/antibiofilm Propertiesmentioning
confidence: 99%
“…), oregano and sage honeys, originated from Epirus Greece, were significantly antimicrobial towards S. aureus ATCC 12600, S. mutans and F. nucleatum . (Voidarou et al., 2021a). Greek pine honey (pH 3.4) was also highly antibacterial against S. marcescens and E. coli comparing to other European (Spanish, British, New Zealand), Cuban, Chilean and Australian honeys (Alnaimat et al., 2012; Serin et al., 2018).…”
Section: Introductionmentioning
confidence: 99%